Over-the-Air OFDM-IM Through Frequency Mixing and Modulating Reconfigurable Intelligent Surfaces - Elvan Kuzucu Hidir; Ertugrul Basar; Hakan Ali Cirpan (IEEE Open Journal of the Communications Society, 2024)
Beyond fifth-generation (5G) wireless communication, reconfigurable intelligent surfaces (RIS) have emerged as a transformative technology that can redefine how we interact with and harness electromagnetic waves. Advancements in meta-materials and metasurfaces have brought about exceptional flexibility in controlling electromagnetic waves at scales smaller than the wavelength. The frequency-mixing RIS (FMx-RIS) has been introduced, considering the benefits of programmable metasurfaces. This method introduces additional frequencies into the original signal, making the communication environment non-linear. Among the different multicarrier transmission methods, orthogonal frequency division multiplexing (OFDM) has become the most commonly used option in wireless communications due to reducing intersymbol interference caused by the frequency selectivity of wireless channels. Upon examining the structure of FMx-RIS, it has been observed that signals similar to OFDM can be obtained at the receiver. This situation indicates the possibility of generating a signal in the air similar to OFDM using an RIS. Therefore, in this study, we propose a novel Over-the-Air OFDM system design by integrating frequency mixing and modulating RIS (FMMx-RIS) to exploit its ability to manipulate the incident wave’s magnitude and frequency. The most notable aspect of this innovative scheme is its ability to offer multi-carrier transmission with a straightforward transmitter structure rather than requiring the complex system design typical of OFDM. The novel concept of index modulation (IM), which leverages the spatial domain to transmit extra information more efficiently, enhancing energy and spectrum efficiency, has attracted considerable interest in both academic and industrial fields. Hence, we extend the system model into the Over-the-Air OFDM-IM system by toggling frequency-changing RIS on and off. Furthermore, we analytically assess the average bit error probability (ABEP) of the proposed Over-the-Air OFDM-IM system using the maximum likelihood (ML) decoder. Subsequently, we present comprehensive computer simulation results to demonstrate the significant improvement in bit error rate (BER) performance of the proposed Over-the-Air OFDM-IM system compared to reference systems employing RIS-aided OFDM.